Factors That Influence Innovative Work Behavior of Y Generation Employees at The Indonesia Financial Services Authority - Gultom, Lasmaida; Nawan Hatiningsi, Katarina; Kali Palindangan, Linus (Journal of World Science, 2022)
This study aims to examine a structural effect model of proactive behavior and workplace spirituality on the innovative work behavior of Generation Y employees at the Indonesia Financial Services Authority (IFSA) mediated by psychological empowerment. The variables in this study are exogenous variables consisting of proactive behavior and workplace spirituality, endogenous variable is innovative work behavior. Psychological empowerment is a mediator. As a hypothesis in this study is a theoretical model of the influence of proactive behavior and workplace spirituality on the innovative work behavior mediated by psychological empowerment fit with the empirical data on Gen Yof IFSA. Data collection techniques are done by self-report measurement, using the scale of proactive behavior, scale of workplace spirituality, scale of psychological empowerment and scale of innovative work behavior. Data analysis used the Structural Equation Model (SEM) with the help of LISREL analysis. The sampling technique was carried out by using simple random sampling with 279 respondents. The results showed that proactive behavior and workplace spirituality have positive and significant effect on innovative work behavior mediated by psychological empowerment, with an RMSEA coefficient of 0.010 and with an GFI coefficient of 0.97, so the hypothesis was accepted.